The ‘Police Change Manager’: Exploring a new leadership paradigm for policing - Smith, Richard (International journal of police science & management, 2019)
The pace, complexity and extent of change in policing are unyielding. Therefore, police leaders must be capable and effective leaders of change. This article provides an exploratory analysis of the experience of police leaders who are responsible for delivering transformational and enduring change, through data collected during a recent study in an urban English police force. The findings show that although positive steps are being taken to improve the way in which change activity is managed and implemented, there is still some way to go. A disconnect was identified between those who are leading change within the headquarters function and their capability to do so. The need to ‘lead for today’ while also ‘leading for tomorrow’ is identified as a key tension at executive level. The article tests the hypotheses that leading change is a specialism of police leadership that should be recognised as such. Implementing the role of the ‘Police Change Manager’ is proposed as the approach by which a more capable and successful change function might be established. The article concludes with recommendations for maturing the approach to change in policing and proposes opportunities for further research. 4241 Enthalten in!366026046!